Extending the GLOBDEF framework with support for semantic enhancement of various data formats. (2nd July 2020) - Nisheva-Pavlova, Maria; Alexandrov, Asen
Semantic enhancement links sections of data files with well-described concepts from some knowledge domain. This allows for further automated reasoning about that data and can be especially useful for extracting value from Big Data. Most of the available enhancement tools focus on specific enhancement needs and data types. In this paper we present our efforts to expand the GLOBDEF framework, introduced in an earlier work, which aims to find a way for processing of large amounts of data and enhancing the data automatically. The framework is designed to leverage a variety of external enhancement tools and has no limitations on the format of the enhanced data. We demonstrate how the framework behaves on a mixed data set of texts and images and explain how an image can be semantically enhanced with a simple automated combination of an object recogniser and a text-based automated enhancer.